2021
DOI: 10.1039/d1ma00571e
|View full text |Cite
|
Sign up to set email alerts
|

Explosive molecule sensing at lattice defect sites in metallic carbon nanotubes

Abstract: Adsorption of a TNT molecule at a divacancy defect on a metallic single walled carbon nanotube. Carbon atoms corresponding to the defect are highlighted in green.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In order to successfully sequence DNA, the development of nanoscale sensors plays a fundamental role. Previous publications have reported that low-dimensional nanomaterials, including heteronanomaterials, can be promising candidates for selective sensing applications, including the detection of explosives, the selective sensing of gases, the detection of environmental pollutants, and the development of biosensors. Regarding DNA sequencing, a number of techniques have been established in the past few years, such as optical selective sensing methods using fluorescent labeling of biomolecules and Sanger sequencing detection approaches (chain termination) for regions of DNA of approximately 900 nucleobase pairs in length. However, such methods are rather expensive and time-consuming. , On the other hand, a variety of alternative and promising strategies based on nanoscale elements have been developed, such as the use of single molecules, which show the possibility of accurately interrogating the nucleobase sequence, , or the use of solid-state nanogaps/nanopores. ,, However, faster, less expensive, and label-free approaches for discriminating small molecules such as the DNA nucleotides are still needed and can be considered highly desired targets of current technology. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In order to successfully sequence DNA, the development of nanoscale sensors plays a fundamental role. Previous publications have reported that low-dimensional nanomaterials, including heteronanomaterials, can be promising candidates for selective sensing applications, including the detection of explosives, the selective sensing of gases, the detection of environmental pollutants, and the development of biosensors. Regarding DNA sequencing, a number of techniques have been established in the past few years, such as optical selective sensing methods using fluorescent labeling of biomolecules and Sanger sequencing detection approaches (chain termination) for regions of DNA of approximately 900 nucleobase pairs in length. However, such methods are rather expensive and time-consuming. , On the other hand, a variety of alternative and promising strategies based on nanoscale elements have been developed, such as the use of single molecules, which show the possibility of accurately interrogating the nucleobase sequence, , or the use of solid-state nanogaps/nanopores. ,, However, faster, less expensive, and label-free approaches for discriminating small molecules such as the DNA nucleotides are still needed and can be considered highly desired targets of current technology. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The discovery of a range of new 2D materials, including graphene, hexagonal boron nitride (hBN), and transition metal dichalcogenides, has been followed by intense research on their potential applications in microelectronics, energy storage, and other fields . Graphene has generated much interest in the electronics industry, for applications ranging from transistors to flexible displays, focused on exploiting its unusual electrical, thermal, and optical properties. , Graphene and other carbon-based materials are also of great interest in sensing applications aimed at the detection of a wide range of toxic gases. The very high specific surface area of monolayer graphene makes it particularly attractive as a gas sensing material …”
mentioning
confidence: 99%